The Influence of Academic Staffing Practices on Quality Assurance Mechanisms in Selected Universities in Uganda - Baiko Ajuaba, David; Ssentamu, Proscovia Namubiru; Marc, Cutright (East African Journal of Education Studies, 2024)
Quality assurance in universities has always been the professional duty of the faculty. In Africa quality assurance mechanisms (QAMs) were initiated as soon as universities were established in the continent. Although in Uganda the teaching staff are at the center of QAMs, inadequacies in academic staffing practices in the areas of remuneration, quality and quantity of the teaching staff have been some of the challenges experienced by universities in the country. This led to the establishment of the National Council for Higher Education to promote QAMs. This study established the extent to which academic staffing practices influenced QAMs in selected universities in Uganda. The study adopted the systems theory where the academic staffs are part of the inputs universities employ to offer services. The study is based on the pragmatic paradigm and cross-sectional survey design. By use of the disproportionate stratified random sampling 180 and 120 students and academic staff members respectively responded to questionnaires. In addition 47 students were conveniently sampled to participate in focus group discussions and 20 managers were purposefully sampled for individual interviews. Descriptive and inferential statistics were employed to analyze and interpret the quantitative data and corroborated with qualitative data. The results presented a mixed picture; chi-square test for the academic staff is not statistically significant and for students is statistically significant. The study concludes that there is moderate influence of academic staffing practices on QAMs in the selected universities in Uganda. In order to enhance QAMs, the study recommends the need to further improve levels of remuneration, quality and number of academic staff in the universities.